Cognitive Decline and Dementia in the Oldest-Old - Kravitz, Efrat (Rambam Health Care Campus, 2012)
The oldest-old are the fastest growing segment of the Western population. Over half of the oldest-old will have dementia, but the etiology is yet unknown. Age is the only risk factor consistently associated with dementia in the oldest-old. Many of the risk and protective factors for dementia in the young elderly, such as ApoE genotype, physical activity, and healthy lifestyle, are not relevant for the oldest-old. Neuropathology is abundant in the oldest-old brains, but specific pathologies of Alzheimer’s disease (AD) or vascular dementia are not necessarily correlated with cognition, as in younger persons. It has been suggested that accumulation of both AD-like and vascular pathologies, loss of synaptic proteins, and neuronal loss contribute to the cognitive decline observed in the oldest-old. Several characteristics of the oldest-old may confound the diagnosis of dementia in this age group. A gradual age-related cognitive decline, particularly in executive function and mental speed, is evident even in non-demented oldest-old. Hearing and vision losses, which are also prevalent in the oldest-old and found in some cases to precede/predict cognitive decline, may mechanically interfere in neuropsychological evaluations. Difficulties in carrying out everyday activities, observed in the majority of the oldest-old, may be the result of motor or physical dysfunction and of neurodegenerative processes. The oldest-old appear to be a select population, who escapes major illnesses or delays their onset and duration toward the end of life. Dementia in the oldest-old may be manifested when a substantial amount of pathology is accumulated, or with a composition of a variety of pathologies. Investigating the clinical and pathological features of dementia in the oldest-old is of great importance in order to develop therapeutic strategies and to provide the most elderly of our population with good quality of life.